Zoom In, Zoom Out. - Anthes, Gary (Communications of the ACM, 2012)
The article discusses the computer technology that enables zooming, or the ability to navigate different levels of information on a computer screen, noting the effects of cost prohibitiveness to the development of advances to zoom technology. It addresses the development of the zoomable user interface (ZUI) including the application ChronoZoom, as well as comments on the issue of web content providing more information than can fit on a computer screen. It notes the development of high-resolution touch screen displays.